Honeycomb type catalyst for low-temperature synergistic removal of VOCs and NOx and preparation method of honeycomb type catalyst
Through the combination of copper, manganese and cerate co-precipitates and surface-treated glass fibers, an efficient honeycomb catalyst was prepared, which solved the problem of coordinated removal of VOCs and NOx under low temperature conditions, simplified the process flow and reduced energy consumption , achieving efficient catalytic effects.
Patent Information
- Application Number
- CN202411531272.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to synergistically and efficiently remove VOCs and NOx from industrial exhaust gas under low temperature conditions, and traditional methods require secondary calcination to increase process flow and energy consumption.
Co-precipitates of copper, manganese and cerium as active component precursors, combined with surface-treated glass fibers and active titanium dioxide, the preparation method of honeycomb catalysts includes co-precipitation, filtration, molding, and aging. , drying and calcining steps to form an efficient low-temperature synergistic removal catalyst.
The synergistic effect of efficient removal of VOCs and NOx under low temperature and low oxygen conditions is achieved, the process flow is simplified, energy consumption is reduced, and the mechanical strength of the catalyst and the anti-ammonium sulfate deposition performance is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial waste gas treatment, and in particular relates to a honeycomb catalyst for synergistically removing VOCs and NOx at low temperature and a preparation method thereof. Background Art
[0002] The catalytic oxidation method has the advantages of low operating temperature, low energy consumption, and a wide range of applications. It is the most promising VOCs removal technology. Selective catalytic reduction (NH3-SCR) is currently the most widely used denitrification technology. In medium and high temperature areas, it is easier to achieve industrial synergistic removal of VOCs and NOx, but under low temperature conditions (180-250°C), the synergistic removal of the two has not been successful. Therefore, how to achieve synergistic treatment of the two and develop commercial catalysts that can synergistically remove VOCs and NOx under low temperature conditions is the main research direction in the industry.
[0003] Catalysts for the synergistic removal of VOCs and NOx at low temperatures have been extensively studied, and are mainly divided into two categories: precious metal and non-precious metal catalysts. Among non-precious metal catalysts, manganese catalysts have abundant surface active sites, high low-temperature activity, low price, and good SCR denitrification activity, and have great commercial potential. Patent CN117019216A discloses a catalyst for the synergistic removal of NOx and VOCs and a preparation method thereof. The method uses manganese cerium as an active component and a molecular sieve as a carrier to obtain a supported high-activity synergistic removal catalyst. The disadvantage is that it requires secondary calcination, which increases the process flow and energy consumption.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to obtain a honeycomb catalyst that can synergistically and efficiently remove VOCs and NOx from industrial tail gas under low temperature and low oxygen conditions while shortening the process flow and saving energy and reducing consumption; at the same time, the preparation process is green, energy-saving, consumption-reducing and short-process.
[0006] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0007] The present invention provides a honeycomb catalyst for low-temperature synergistic removal of VOCs and NOx. The raw and auxiliary materials of the honeycomb catalyst include: an active component precursor, a carrier component and a strength auxiliary material; the mass ratio of the active component precursor, the carrier component and the strength auxiliary material is 8-20:55-75:15-30;
[0008] The active component precursor is a co-precipitate of acid salts of copper, manganese and cerium;
[0009] The strength auxiliary material is glass fiber treated with a coating liquid containing silicon and titanium elements.
[0010] Preferably, the support component is active titanium dioxide.
[0011] The present invention provides a method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx at low temperature, comprising the following steps:
[0012] 1) Preparing an active component precursor: adding a coprecipitant to a mixed solution containing a copper salt, a manganese salt, and a cerium salt to obtain a coprecipitate of copper, manganese, and cerium salts, and filtering and removing the liquid to obtain an active component precursor;
[0013] 2) Preparing strength auxiliary materials: soaking glass fiber in a coating liquid containing silicon and titanium elements, and taking it out to obtain strength auxiliary materials;
[0014] 3) preparing a clay material: adding the active component precursor obtained in step 1), the strength auxiliary material obtained in step 2), and the molding auxiliary agent to the carrier component in order to obtain a clay material;
[0015] 4) preparing a honeycomb catalyst blank: the clay obtained in step 3) is kneaded, moved into a mold and extruded to obtain a honeycomb catalyst blank;
[0016] 5) Drying and calcining: The honeycomb catalyst blank obtained in step 4) is aged, dried, baked, and calcined to obtain a honeycomb catalyst.
[0017] Preferably, in step 1), the molar ratio of the total amount of copper, manganese and cerium in the coprecipitant and the mixed solution is 1.05 to 1.2:1;
[0018] The temperature of the coprecipitant is controlled at 38-80°C; the reaction temperature of the mixed solution is controlled at 45-80°C; the reaction time of the coprecipitant solution and the mixed solution is 0.2-1.5h;
[0019] The mass fraction of the acid salt co-precipitate after pressure filtration and deliquoring is controlled to be 65% to 85%;
[0020] Preferably, the concentration of the coprecipitant solution is 550-620 g / L.
[0021] Preferably, the total mass fraction of copper salt, manganese salt and cerium salt in the mixed solution is 200-280 g / L; the molar ratio of copper salt, manganese salt and cerium salt is 1-3:1-3:4-8,
[0022] Preferably, the coprecipitant is an aqueous oxalic acid solution or an ammonium carbonate solution;
[0023] The mixed solution is obtained by dissolving acid salts of copper, manganese and cerium in a mixed solvent of water, ethanol and glycerol;
[0024] Preferably, the acid salt of copper, manganese and cerium comprises acetate of copper, manganese and cerium and / or nitrate of copper, manganese and cerium;
[0025] Preferably, the acetates of copper, manganese and cerium comprise: hydrated copper acetate, hydrated manganese triacetate and hydrated cerium acetate;
[0026] Preferably, the nitrates of copper, manganese and cerium comprise: copper nitrate, manganese nitrate and cerium nitrate;
[0027] Preferably, the mass ratio of water, ethanol and glycerol in the mixed solvent is 100:10-25:3-15.
[0028] Preferably, in step 2), the glass fiber is immersed for 0.2 to 1 hour, and the weight gain of the glass fiber after coating is controlled to be 5% to 25%;
[0029] The mass fraction of silicon in the coating liquid is 5% to 12%, and the mass fraction of titanium is 7% to 18%;
[0030] Preferably, the coating liquid is composed of a titanium affinity agent, a wetting and dispersing agent and a first solvent, and the mass ratio thereof is 0.3-2:0.5-3:1;
[0031] Preferably, the titanophilic agent comprises a titanate ester, which is a mixture of one or more of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropoxy titanium and isooctyl titanate;
[0032] Preferably, the wetting and dispersing agent comprises alkoxysilane, which is a mixture of one or more of octadecyltrimethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, tetraethoxysilane, tetrabutoxysilane and methylsilane;
[0033] Preferably, the first solvent is glycerol or a non-aqueous solvent containing glycerol.
[0034] Preferably, in step 3), the mass ratio of the active component precursor, the carrier component, the strength auxiliary material and the molding auxiliary agent is 8-20:55-75:15-30:4-10;
[0035] Preferably, the molding aid comprises a pH adjuster, a lubricant, a pore former, and a second solvent;
[0036] Preferably, the pH adjuster includes one of sodium hydroxide, ammonia water or liquid ammonia, and the pH value is between 8 and 12;
[0037] Preferably, the lubricant is epoxy oleate or phthalate, and the amount of the lubricant added is 0.1% to 0.4% of the mass of the carrier component;
[0038] Preferably, the pore-forming agent is biomass fiber powder, and the amount of the pore-forming agent added is 1% to 3% of the mass of the carrier component;
[0039] Preferably, the second solvent is a liquid mixed with glycerol and water in a mass ratio of 0.5 to 3:1.
[0040] Preferably, in step 5), aging and drying: placing the honeycomb catalyst blank in an environment of 45 to 60° C. for 24 to 72 hours, and controlling the relative humidity at 85% to 95%;
[0041] The drying temperature is 105-130°C and the drying time is 3-24 hours;
[0042] The calcination temperature is 350-480°C, the calcination time is maintained at 1-6 hours, and the heating rate is 1-10°C / min.
[0043] Beneficial effects of the present invention:
[0044] 1) The active component precursor used in the present invention does not need to be dried, calcined or the like, and can directly enter the subsequent mixing and molding process, thereby shortening and simplifying the preparation process.
[0045] 2) The present invention uses copper and manganese as main catalytic components and high-content cerium as a catalytic promoter, which improves the oxygen storage and oxygen transfer capacity of the catalyst. The resulting honeycomb catalyst has a wide active temperature window, especially under low temperature and low oxygen conditions, and has better application prospects.
[0046] 3) The present invention uses glass fiber with special surface treatment as strength auxiliary material, which greatly improves the mechanical strength of the obtained catalyst. In addition, the introduction of silicon element improves the anti-ammonium sulfate salt deposition performance of the honeycomb catalyst.
[0047] 4) The raw and auxiliary materials used in the present invention are cheap and easily available, the operation is simple, the reaction conditions are mild and controllable, and it is easy to realize industrialization, and has good commercial value and market competitiveness. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Where the ratio of substances is not indicated in the embodiments, it should be understood that they can be matched in any ratio. Where the unit of the ratio of substances is not indicated, it should be understood that it is a mass ratio.
[0050] First, the present invention is explained as a whole. The present invention is divided into three parts for explanation, which are as follows:
[0051] The first part of the present invention is to provide a honeycomb catalyst for synergistically removing VOCs and NOx. The honeycomb catalyst can synergistically and efficiently remove VOCs and NOx from industrial tail gas, and is particularly suitable for tail gas working conditions with low temperature (180-250°C) and low oxygen concentration. The raw and auxiliary materials used in the preparation of the honeycomb catalyst include: active component precursor, carrier component, strength auxiliary material, and molding aid. After batching and mixing, kneading and molding, aging and drying, drying, and calcining, the catalyst is obtained.
[0052] The catalyst has the characteristics of easy preparation, low cost, high activity, etc., and has broad application prospects. It has the advantages of economical raw materials, convenient operation, controllable reaction conditions, reduced environmental pollution and continuous operation.
[0053] The second part of the present invention is to explain the composition and preparation method of the raw and auxiliary materials used in the catalyst of the present invention. The raw and auxiliary materials include: active component precursor, carrier component, strength auxiliary material, and molding auxiliary agent.
[0054] 1. The active component precursor of the present invention is an oxalate co-precipitate of copper, manganese and cerium. The preparation scheme is as follows: an oxalic acid aqueous solution (solution A) is uniformly added to a rapidly stirred copper, manganese and cerium salt solution (solution B) to obtain a copper, manganese and cerium oxalate co-precipitate, and the obtained co-precipitate is filtered and deliquated to obtain the product.
[0055] Alternatively, the active component precursor of the present invention is a carbonate co-precipitate of copper, manganese and cerium, and the preparation scheme is as follows: an ammonium carbonate aqueous solution (solution A) is uniformly added to a rapidly stirred copper, manganese and cerium salt solution (solution B) to obtain a carbonate co-precipitate of copper, manganese and cerium, and the obtained co-precipitate is filtered and deliquated to obtain the product.
[0056] a. The temperature of solution A is 38-80°C and the concentration is 550-620g / L.
[0057] b. The solution B is obtained by dissolving hydrated copper acetate, hydrated manganese triacetate and hydrated cerium acetate in a mixed solvent of water, ethanol and glycerol; or, the solution B is obtained by dissolving copper nitrate, manganese nitrate and cerium nitrate in a mixed solvent of water, ethanol and glycerol.
[0058] c. The mass ratio of water, ethanol and glycerol in the mixed solvent is 100:10-25:3-15.
[0059] d. The molar ratio of the copper, manganese and cerium salts is 1 to 3:1 to 3:4 to 8. Preferably, the molar ratio of copper, manganese and cerium is 1:1:4.
[0060] e. Control the temperature of solution B at 45 to 80°C, preferably, control the temperature of the solution at 60 to 70°C,
[0061] f. The total mass fraction of copper, manganese and cerium salts in solution B is 200-280 g / L.
[0062] g. The molar ratio of the total amount of copper, manganese and cerium in solution A to the mixed solution B is 1.05 to 1.2:1.
[0063] h. The reaction time of solution A and solution B is 0.2 to 1.5 hours.
[0064] i. The mass fraction of the oxalate co-precipitate or carbonate co-precipitate after pressure filtration and dehydration is controlled to be 65% to 85%.
[0065] In the above preparation process: the purpose of controlling the higher temperature of solutions A and B is to increase the solubility of the solute and accelerate the reaction. The purpose of adding ethanol is to further increase the solubility of copper, manganese and cerium salts, obtain a high-concentration active component liquid, and quickly react with oxalic acid to form an oxalate coprecipitate, or quickly react with ammonium carbonate to form a carbonate coprecipitate. The purpose of adding glycerol is to change the viscosity of the solution and inhibit the growth of the coprecipitate grains. In addition, the residual glycerol in the coprecipitate can improve the plasticity of the mud in the subsequent preparation process, and has the dual functions of a lubricant and a pore-forming agent during the molding and calcining process.
[0066] In terms of the design of the active components of the catalyst, the present invention uses copper and manganese as the main catalytic components and a high content of cerium as a catalytic aid. Cerium ions have a variety of valence states, low energy barriers between valence states, variable valence states, and strong oxygen storage capacity. In addition, it can overlap with the p orbitals of adjacent atoms, easily produce lattice oxygen vacancies, and trigger crystal plane rearrangement and oxygen migration. This catalyst with high oxygen storage and oxygen migration capacity combined with the high catalytic oxidation activity of copper and manganese has a wide active temperature window, which is particularly suitable for use in low temperature and low oxygen concentration scenarios.
[0067] 2. The carrier component of the present invention is active titanium dioxide.
[0068] 3. The strength auxiliary material of the present invention is a surface-treated glass fiber, and the preparation scheme is as follows:
[0069] The prepared glass fiber is soaked in the coating liquid for 0.2 to 1 hour and then taken out. The weight gain of the glass fiber after coating is controlled to be 5% to 25%, preferably 9% to 15%.
[0070] a. The coating liquid is composed of a titanium affinity agent, a wetting and dispersing agent, and a first solvent in a mass ratio of 0.3 to 2:0.5 to 3:1.
[0071] b. The mass fraction of silicon in the coating liquid is 5% to 12%, and the mass fraction of titanium is 7% to 18%
[0072] c. The titanium affinity agent is a titanate, which is a mixture of one or more of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropoxy titanium and isooctyl titanate.
[0073] d. The wetting and dispersing agent is an alkoxysilane, which is a mixture of one or more of octadecyltrimethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, tetraethoxysilane, tetrabutoxysilane and methylsilane.
[0074] e. The first solvent is glycerol or a non-aqueous solvent containing glycerol.
[0075] After the immersion treatment, a titanium-philic transition layer molecular film is formed on the surface of the glass fiber. In the subsequent stirring and mud-making process, the polarity transfer occurs during the hydrolysis process of silicon and titanium in the transition layer, and the surface viscosity is reduced, which is conducive to the uniform dispersion of the glass fiber and avoids deformation and cracking of the catalyst during the drying and calcining process. The second beneficial effect of the immersion treatment is that the hydrolyzed silicon hydroxyl, titanium hydroxyl and carrier titanium surface hydroxyl groups are dehydrated and condensed during the subsequent drying and calcining process. This process firmly combines the carrier titanium and the glass fiber, and the mechanical strength of the resulting catalyst is greatly improved. In addition, the benefit of introducing silicon in terms of catalytic activity is that it can inhibit the deposition of ammonium sulfate on the catalyst surface at low temperatures, thereby improving the low-temperature sulfur resistance of the catalyst.
[0076] 4. The molding aid of the present invention comprises a pH regulator, a lubricant, a pore former, and a second solvent.
[0077] a. The pH regulator is sodium hydroxide, ammonia water or liquid ammonia, preferably ammonia water, and the pH value of the molding mud is controlled to be 8 to 12. Preferably, the pH value is controlled to be 9 to 11.
[0078] b. The lubricant is epoxy oleate or phthalate, and the added amount is 0.1% to 0.4% of the mass of the carrier component.
[0079] c. The pore-forming agent is biomass fiber powder, and the addition amount is 1% to 3% of the carrier component mass. The first function of the pore-forming agent is to act as a strength aid to enhance the rigidity of the formed blank, and secondly, to leave a developed pore structure and internal stress release space for the catalyst after calcination and burnout.
[0080] d. The second solvent is a mixture of glycerol and water in a mass ratio of 0.5 to 3:1. The role of glycerol in the catalyst preparation process is to improve the plasticity of the molding mud. In addition, it has the effect of a pore-forming agent during the calcination process.
[0081] The third part of the present invention is to provide a technical solution for preparing the catalyst of the present invention. The preparation steps include: batching and mixing, kneading and shaping, aging and drying, drying, and calcining.
[0082] Batching and mixing: Add active component precursor, strength auxiliary material and molding auxiliary agent to the carrier component in order and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, carrier component, strength auxiliary material and molding auxiliary agent is 8-20:55-75:15-30:4-10.
[0083] Clay kneading and molding: After the clay is kneaded in a vacuum clay kneading machine, it is moved into a mold and extruded to obtain a honeycomb catalyst blank. Preferably, the extrusion can be repeated multiple times to improve the plasticity and isotropy of the clay.
[0084] Aging and drying: Place the blank in an environment of 45-60°C for 24-72 hours and control the relative humidity at 85%-95%.
[0085] Drying: Keep the blank at 105-130℃ for 3-24h.
[0086] Calcination: Keep the blank at 350-480°C for 1-6 hours, with a heating rate of 1-10°C / min. Preferably, keep it at 380-410°C for 2-3 hours, with a heating rate of 3-5°C / min. More preferably, keep it at 270-295°C for 0.5-3 hours during the heating process and then continue to heat up for calcination. The purpose of staying at 270-295°C is to allow the volatile components and burnable components in the catalyst to volatilize or oxidize and burn in advance, so as to avoid the concentrated release of high temperature and stress during the subsequent heating process of the catalyst.
[0087] In summary, the present invention uses copper and manganese as main catalytic components, high-content cerium as a catalytic aid, specially treated glass fiber as a strength auxiliary material, and a molding aid. After mixing the ingredients, kneading the clay, aging and drying, baking, and calcining, a high-strength, high-activity honeycomb catalyst for synergistically removing VOCs and NOx is obtained.
[0088] Example 1
[0089] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0090] The preparation scheme of S1 active component precursor is as follows:
[0091] a. Take 580 kg of oxalic acid dihydrate and add it to 75℃ deionized water at a uniform speed. Heat and keep the liquid temperature at 75℃. Continue stirring until it is completely dissolved and adjust the volume to 1 ml. 3 Solution A was obtained.
[0092] b. Prepare a mixed solvent of water, ethanol and glycerol in a mass ratio of 100:20:10 and heat it to 65°C. Weigh 240 kg of acetate hydrates of copper, manganese and cerium in a molar ratio of 2:2:6 and add them to the mixed solvent at a uniform rate. Heat and maintain the liquid temperature at 65°C. Continue stirring until completely dissolved and adjust the volume to 1 ml. 3 Solution B was obtained.
[0093] c. The volume ratio of solution A and solution B was calculated based on the molar ratio of the solute components oxalic acid and acetate being 1.1:1. Solution A was added to the rapidly stirred solution B at a uniform rate according to the volume ratio, and the stirring reaction was continued for 1.0 h to obtain the oxalate co-precipitate of copper, manganese and cerium.
[0094] d. Use pressure filtration to remove liquid and control the mass fraction of oxalate co-precipitate to 75% to obtain the active component precursor used to prepare the catalyst.
[0095] The preparation scheme of S2 strength auxiliary materials is as follows (surface treatment of glass fiber):
[0096] a. Prepare a titanate mixed solution according to the mass fraction of titanium element in the coating solution of 13%. The mixed solution is obtained by mixing tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropoxy titanium and isooctyl titanate according to the calculated proportion.
[0097] b. Prepare an alkoxysilane mixed solution according to the mass fraction of silicon element in the coating solution of 9%. The mixed solution is obtained by mixing octadecyltrimethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, tetraethoxysilane, tetrabutoxysilane and methylsilane according to the calculated proportion.
[0098] c. The titanate mixed liquid, the alkoxysilane mixed liquid, and the non-aqueous solvent containing glycerol are mixed in a mass ratio of 1:1:1 to obtain a coating liquid.
[0099] d. The glass fiber was soaked in the coating solution for 0.6 h and then taken out. The weight gain of the glass fiber after coating was controlled to be 12%, and the strength auxiliary material (surface-treated glass fiber) used for preparing the catalyst was obtained.
[0100] The preparation scheme of S3 molding additive is as follows:
[0101] 0.25% (relative to the mass fraction of the carrier component) of phthalate and 2% (relative to the mass fraction of the carrier component) of biomass fiber powder are added to a mixed solvent of propylene glycol and water in a mass ratio of 1.5:1, mixed evenly, and then the pH value is adjusted to 10 with liquid ammonia.
[0102] The preparation scheme of S4 honeycomb catalyst is as follows:
[0103] a. Add active component precursor, strength auxiliary material and molding auxiliary agent to active titanium dioxide in sequence and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, active titanium dioxide, strength auxiliary material and molding auxiliary agent is 14:65:22:7.
[0104] b. After the clay is kneaded using a vacuum kneading machine, it is moved into a mold and extruded repeatedly for more than 3 times, and then extruded to obtain a honeycomb catalyst blank.
[0105] c. Place the blank in an environment of 52°C for 48 hours and control the relative humidity at 90%.
[0106] d. Dry the blank at 118°C for 14 hours.
[0107] e. The dried blank was heated to 285°C at a rate of 4°C / min, maintained for 2 hours, and then heated to 400°C, maintained for 2.5 hours. The blank was cooled and taken out to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0108] Example 2
[0109] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0110] The preparation scheme of S1 active component precursor is as follows:
[0111] a. Take 620 kg of oxalic acid dihydrate and add it to 80℃ deionized water at a uniform speed. Heat and keep the liquid temperature at 80℃. Continue stirring until it is completely dissolved and adjust the volume to 1 ml. 3 Solution A was obtained.
[0112] b. Prepare a mixed solvent of water, ethanol and glycerol in a mass ratio of 100:25:15 and heat it to 80°C. Add 280 kg of acetate hydrates of copper, manganese and cerium in a molar ratio of 1:1:4 to the mixed solvent at a uniform rate. Heat and maintain the liquid temperature at 80°C. Continue stirring until completely dissolved and adjust the volume to 1 ml. 3 Solution B was obtained.
[0113] c. The volume ratio of solution A and solution B was calculated based on the molar ratio of the solute components oxalic acid and acetate of 1.2:1. Solution A was added to the rapidly stirred solution B at a uniform rate according to the volume ratio, and the stirring reaction was continued for 1.5 hours to obtain the oxalate co-precipitate of copper, manganese and cerium.
[0114] d. Use pressure filtration to remove liquid and control the mass fraction of oxalate co-precipitate to 85% to obtain the active component precursor used to prepare the catalyst.
[0115] Steps S2, S3, and S4 adopt the same preparation scheme as that of Example 1 to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0116] Example 3
[0117] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0118] The preparation scheme of S1 active component precursor is as follows:
[0119] a. Take 550 kg of oxalic acid dihydrate and add it to 68°C deionized water at a uniform speed. Heat and keep the liquid temperature at 68°C. Continue stirring until it is completely dissolved and adjust the volume to 1 ml. 3 Solution A was obtained.
[0120] b. Prepare a mixed solvent of water, ethanol and glycerol in a mass ratio of 100:10:3 and heat it to 45°C. Weigh 200 kg of acetate hydrates of copper, manganese and cerium in a molar ratio of 3:3:8 and add them to the mixed solvent at a uniform rate. Heat and maintain the liquid temperature at 45°C. Continue stirring until completely dissolved and adjust the volume to 1 ml. 3 Solution B was obtained.
[0121] c. The volume ratio of solution A and solution B was calculated based on the molar ratio of the solute components oxalic acid and acetate of 1.05:1. Solution A was added to the rapidly stirred solution B at a uniform rate according to the volume ratio, and the stirring reaction was continued for 0.2 h to obtain the oxalate co-precipitate of copper, manganese and cerium.
[0122] d. Use pressure filtration to remove liquid and control the mass fraction of oxalate co-precipitate to 65% to obtain the active component precursor used to prepare the catalyst.
[0123] Steps S2, S3, and S4 adopt the same preparation scheme as that of Example 1 to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0124] Example 4
[0125] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0126] The preparation scheme of S2 strength auxiliary materials is as follows (surface treatment of glass fiber):
[0127] a. Prepare a titanate mixed solution according to the mass fraction of titanium element in the coating solution of 18%. The mixed solution is obtained by mixing tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropoxy titanium and isooctyl titanate according to the calculated proportion.
[0128] b. Prepare an alkoxysilane mixed solution according to the mass fraction of silicon element in the coating solution of 12%. The mixed solution is obtained by mixing octadecyltrimethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, tetraethoxysilane, tetrabutoxysilane and methylsilane according to the calculated proportion.
[0129] c. The titanate mixed liquid, the alkoxysilane mixed liquid, and the non-aqueous solvent containing glycerol are mixed in a mass ratio of 2:3:1 to obtain a coating liquid.
[0130] d. The glass fiber was soaked in the coating solution for 1 hour and then taken out. The weight gain of the glass fiber after coating was controlled to be 15%, and the strength auxiliary material (surface-treated glass fiber) used for preparing the catalyst was obtained.
[0131] Steps S1, S3 and S4 adopt the same preparation scheme as that in Example 1 to prepare a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0132] Example 5
[0133] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0134] The preparation scheme of S2 strength auxiliary materials is as follows (surface treatment of glass fiber):
[0135] a. Prepare a titanate mixed solution according to the mass fraction of titanium element in the coating solution of 7%. The mixed solution is obtained by mixing tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropoxy titanium and isooctyl titanate according to the calculated proportion.
[0136] b. Prepare an alkoxysilane mixed solution according to the mass fraction of silicon element in the coating solution of 5%. The mixed solution is obtained by mixing octadecyltrimethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, tetraethoxysilane, tetrabutoxysilane and methylsilane according to the calculated proportion.
[0137] c. The titanate mixed solution, the alkoxysilane mixed solution, and the non-aqueous solvent containing glycerol are mixed in a mass ratio of 0.3:0.5:1 to obtain a coating liquid.
[0138] d. The glass fiber was soaked in the coating solution for 0.2 h and then taken out. The weight gain of the glass fiber after coating was controlled to be 5%, and the strength auxiliary material (surface-treated glass fiber) used for preparing the catalyst was obtained.
[0139] Steps S1, S3 and S4 adopt the same preparation scheme as that of Example 1 to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0140] Example 6
[0141] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0142] The preparation scheme of S3 molding additive is as follows:
[0143] 0.4% (relative to the mass fraction of the carrier component) of phthalate and 3% (relative to the mass fraction of the carrier component) of biomass fiber powder are added to a mixed solvent of propylene glycol and water in a mass ratio of 3:1, and the mixture is evenly mixed and then the pH value is adjusted to 12 with liquid ammonia.
[0144] Steps S1, S2, and S4 adopt the same preparation scheme as in Example 1 to prepare a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0145] Example 7
[0146] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0147] The preparation scheme of S3 molding additive is as follows:
[0148] 0.1% (relative to the mass fraction of the carrier component) of epoxy oleate and 1% (relative to the mass fraction of the carrier component) of biomass fiber powder are added to a mixed solvent of propylene glycol and water in a mass ratio of 0.5:1, mixed evenly, and then the pH value is adjusted to 8 with liquid ammonia.
[0149] Steps S1, S2, and S4 adopt the same preparation scheme as in Example 1 to prepare a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0150] Example 8
[0151] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0152] Steps S1, S2 and S3 adopt the same preparation scheme as in Example 1.
[0153] The preparation scheme of S4 catalyst is as follows:
[0154] a. Add active component precursor, strength auxiliary material and molding auxiliary agent to active titanium dioxide in sequence and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, active titanium dioxide, strength auxiliary material and molding auxiliary agent is 20:75:30:10.
[0155] b. After the clay is kneaded using a vacuum kneading machine, it is moved into a mold and extruded repeatedly for more than 3 times, and then extruded to obtain a honeycomb catalyst blank.
[0156] c. Place the blank in an environment of 60°C for 72 hours and control the relative humidity at 95%.
[0157] d. Dry the blank at 130℃ for 24h.
[0158] e. The dried blank was first heated to 295°C at a rate of 10°C / min, maintained for 3 hours, and then heated to 410°C, maintained for 6 hours. The blank was cooled and taken out to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0159] Example 9
[0160] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0161] Steps S1, S2 and S3 adopt the same preparation scheme as in Example 1.
[0162] The preparation scheme of S4 catalyst is as follows:
[0163] a. Add active component precursor, strength auxiliary material and molding auxiliary agent to active titanium dioxide in sequence and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, active titanium dioxide, strength auxiliary material and molding auxiliary agent is 8:55:15:4.
[0164] b. After the clay is kneaded using a vacuum kneading machine, it is moved into a mold and extruded repeatedly for more than 3 times, and then extruded to obtain a honeycomb catalyst blank.
[0165] c. Place the blank in an environment of 45°C for 24 hours and control the relative humidity at 85%.
[0166] d. Dry the blank at 105℃ for 3h.
[0167] e. The dried blank was heated to 270°C at a rate of 1°C / min, maintained for 0.5h, and then heated to 380°C, maintained for 1h. The blank was cooled and taken out to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0168] Example 10
[0169] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0170] Steps S1, S2 and S3 adopt the same preparation scheme as in Example 1.
[0171] The preparation scheme of S4 catalyst is as follows:
[0172] a. Add active component precursor, strength auxiliary material and molding auxiliary agent to active titanium dioxide in sequence and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, active titanium dioxide, strength auxiliary material and molding auxiliary agent is 16:60:20:8.
[0173] b. After the clay is kneaded using a vacuum kneading machine, it is moved into a mold and extruded repeatedly for more than 3 times, and then extruded to obtain a honeycomb catalyst blank.
[0174] c. Place the blank in an environment of 55°C for 60 hours and control the relative humidity at 88%.
[0175] d. Dry the blank at 115℃ for 8h.
[0176] e. The dried blank was first heated to 280°C at a rate of 6°C / min, maintained for 1 hour, and then heated to 390°C, maintained for 2 hours. The blank was cooled and taken out to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0177] Embodiment 11
[0178] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0179] The preparation scheme of S1 active component precursor is as follows:
[0180] a. Take 550 kg of ammonium carbonate and add it to 38°C deionized water at a uniform speed. Heat and keep the liquid temperature at 38°C. Continue stirring until it is completely dissolved and adjust the volume to 1 ml. 3 Solution A was obtained.
[0181] b. Prepare a mixed solvent of water, ethanol and glycerol in a mass ratio of 100:20:10 and heat it to 65°C. Weigh 240 kg of acetate hydrates of copper, manganese and cerium in a molar ratio of 2:2:6 and add them to the mixed solvent at a uniform rate. Heat and maintain the liquid temperature at 65°C. Continue stirring until completely dissolved and adjust the volume to 1 ml. 3 Solution B was obtained.
[0182] c. The volume ratio of solution A and solution B is calculated based on the molar ratio of solute components ammonium carbonate to acetate of 1.1:1. Solution A is added to the rapidly stirred solution B at a uniform rate according to the volume ratio, and the stirring reaction is continued for 1.0 h to obtain a carbonate coprecipitate of copper, manganese and cerium.
[0183] d. Use pressure filtration to remove liquid and control the mass fraction of carbonate co-precipitate to 75% to obtain the active component precursor used to prepare the catalyst.
[0184] Steps S2, S3, and S4 adopt the same preparation scheme as that of Example 1 to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0185] Example 12
[0186] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0187] The preparation scheme of S1 active component precursor is as follows:
[0188] a. Take 580 kg of oxalic acid dihydrate and add it to 75℃ deionized water at a uniform speed. Heat and keep the liquid temperature at 75℃. Continue stirring until it is completely dissolved and adjust the volume to 1 ml. 3 Solution A was obtained.
[0189] b. Prepare a mixed solvent of water, ethanol and glycerol in a mass ratio of 100:20:10 and heat it to 65°C. Add 240 kg of nitrate hydrates of copper, manganese and cerium in a molar ratio of 2:2:6 at a uniform rate to the mixed solvent, heat and maintain the liquid temperature at 65°C, continue stirring until completely dissolved and adjust the volume to 1 m 3 Solution B was obtained.
[0190] c. The volume ratio of solution A and solution B was calculated based on the molar ratio of the solute components oxalic acid and acetate being 1.1:1. Solution A was added to the rapidly stirred solution B at a uniform rate according to the volume ratio, and the stirring reaction was continued for 1.0 h to obtain the oxalate co-precipitate of copper, manganese and cerium.
[0191] d. Use pressure filtration to remove liquid and control the mass fraction of oxalate co-precipitate to 75% to obtain the active component precursor used to prepare the catalyst.
[0192] Steps S2, S3, and S4 adopt the same preparation scheme as that of Example 1 to obtain a honeycomb catalyst for synergistic removal of VOCs and NOx.
[0193] Comparative Example 1
[0194] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0195] The preparation scheme of S1 active component precursor is as follows:
[0196] a. Take 580 kg of oxalic acid dihydrate and add it to 75℃ deionized water at a uniform speed. Heat and keep the liquid temperature at 75℃. Continue stirring until it is completely dissolved and adjust the volume to 1 ml. 3 Solution A was obtained.
[0197] b. Prepare a mixed solvent of water, ethanol and glycerol in a mass ratio of 100:20:10 and heat it to 65°C. Weigh 240 kg of acetate hydrates of copper, manganese and cerium in a molar ratio of 2:2:6 and add them to the mixed solvent at a uniform rate. Heat and maintain the liquid temperature at 65°C. Continue stirring until completely dissolved and adjust the volume to 1 ml. 3 Solution B was obtained.
[0198] c. The volume ratio of solution A and solution B was calculated based on the molar ratio of the solute components oxalic acid and acetate being 1.1:1. Solution A was added to the rapidly stirred solution B at a uniform rate according to the volume ratio, and the stirring reaction was continued for 1.0 h to obtain the oxalate co-precipitate of copper, manganese and cerium.
[0199] d. The oxalate co-precipitate was heated to 400°C, maintained for 2 hours, and then cooled and taken out to obtain the active component precursor used to prepare the catalyst.
[0200] Steps S2, S3 and S4 adopt the same preparation scheme as that of Example 1 to prepare a comparative example honeycomb catalyst.
[0201] Comparative Example 2
[0202] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0203] S2 uses untreated glass fiber directly as a strength auxiliary material for the preparation of the catalyst.
[0204] Steps S1, S3 and S4 adopt the same preparation scheme as that of Example 1 to prepare a comparative example honeycomb catalyst.
[0205] Comparative Example 3
[0206] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0207] Steps S1, S2 and S3 adopt the same preparation scheme as in Example 1.
[0208] The preparation scheme of S4 catalyst is as follows:
[0209] a. Add active component precursor, strength auxiliary material and molding auxiliary agent to active titanium dioxide in sequence and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, active titanium dioxide, strength auxiliary material and molding auxiliary agent is 16:60:20:8.
[0210] b. After the clay is kneaded using a vacuum kneading machine, it is moved into a mold and extruded repeatedly for more than 3 times, and then extruded to obtain a honeycomb catalyst blank.
[0211] c. Place the blank in an environment of 55°C for 60 hours and control the relative humidity at 88%.
[0212] d. Dry the blank at 115℃ for 8h.
[0213] e. The dried blank was heated to 390°C at a rate of 6°C / min and maintained at that temperature for 2 hours. Then the blank was cooled and taken out to obtain a comparative honeycomb catalyst.
[0214] Comparative Example 4
[0215] A method for preparing a honeycomb catalyst for synergistically removing VOCs and NOx and a pretreatment process of raw and auxiliary materials used therein, comprising the following steps:
[0216] Steps S1, S2 and S3 adopt the same preparation scheme as in Example 1.
[0217] The preparation scheme of S4 catalyst is as follows:
[0218] a. Add active component precursor, strength auxiliary material and molding auxiliary agent to active titanium dioxide at the same time and stir evenly to obtain the catalyst mud. The mass ratio of active component precursor, active titanium dioxide, strength auxiliary material and molding auxiliary agent is 16:60:20:8.
[0219] b. After the mud is kneaded in a vacuum kneading machine, it is moved into a mold without repeated extrusion, and directly extruded to obtain a honeycomb catalyst blank.
[0220] c. Place the blank in an environment of 55°C for 60 hours and control the relative humidity at 88%.
[0221] d. Dry the blank at 115℃ for 8h.
[0222] e. The dried blank was heated to 390°C at a rate of 6°C / min and maintained at that temperature for 2 hours. Then the blank was cooled and taken out to obtain a comparative honeycomb catalyst.
[0223] The performance test methods for the embodiments and comparative examples of the present invention are as follows:
[0224] Mechanical strength test method: According to the test method for the wear rate of honeycomb flue gas denitration catalyst (GB / T31587-2015), the maximum pressure value is read when the pressure drops sharply by continuous pressurization. The test results are shown in Table 1.
[0225] Catalyst NOx removal activity test conditions: reaction temperature 240°C, catalyst loading volume 5cm×5cm×200cm, simulated gas flow rate 25Nm 3 / h, NO concentration 500ppm, ammonia nitrogen molar ratio = 1.0, oxygen concentration 4.5%, water content 8.0%, nitrogen as the balance gas.
[0226] The catalyst VOCs removal activity test used toluene, propane and dichloromethane as model compounds. The test conditions were: reaction temperature 240°C, catalyst loading volume 5cm×5cm×200cm, simulated gas flow rate 25Nm 3 / h, VOCs concentration 1000ppm, oxygen concentration 4.5%, water content 8.0%, nitrogen as the balance gas.
[0227] Table 1 Test results of catalyst strength obtained in Examples 1, 4, 6, 8, 10, 11, 12 and Comparative Examples 1-4
[0228]
[0229] Table 2 Catalytic activity test results of the catalysts obtained in Examples 1, 4, 6, 8, 10, 11, 12 and Comparative Examples 1-4
[0230]
[0231]
[0232] The results of Comparative Example 1 and Example 1 show that the calcination treatment of the coprecipitate in step S1 has no beneficial effect on the strength and activity of the catalyst and is not necessary.
[0233] The results of Comparative Example 2 and Example 1 show that when untreated glass fiber is directly used as a strength auxiliary material for the preparation of the catalyst, the activity of the catalyst does not change significantly, but its mechanical strength is significantly reduced.
[0234] The results of Comparative Example 3 and Example 1 show that after the intermediate retention step is omitted during the calcination of the catalyst, the strength and activity of the catalyst both decrease slightly. This is because the volatile components in the catalyst are concentratedly oxidized and release heat during the calcination process, causing local short-term overheating and causing a certain degree of damage to its microstructure.
[0235] The results of Comparative Example 4 and Example 1 show that the order of mixing ingredients and whether to repeat extrusion have a significant effect on the mechanical strength of the catalyst. Adding active component precursors, strength auxiliary materials, and molding aids to the active titanium dioxide in the order of stirring evenly, combined with repeated extrusion before extrusion molding, can avoid the decrease in strength caused by poor mixing.
[0236] The catalyst of the present invention uses the acid salt coprecipitate of copper, manganese and cerium as the active component precursor used by the catalyst, uses active titanium dioxide as the carrier component, uses glass fiber with a specially treated surface as the strength auxiliary material, and then mixes with a molding auxiliary agent. After batching and mixing, mud molding, aging and drying, drying, and calcining, a honeycomb-type collaborative removal catalyst with high mechanical strength and high catalytic activity is obtained. The obtained catalyst has a wide active temperature window, is resistant to ammonium sulfate deposition, and is particularly suitable for low temperature (180-250° C.) and low oxygen use conditions. In addition, the raw and auxiliary materials used in the present invention are cheap and easy to obtain, the preparation process is green, low-consumption, and short, and has good application prospects and market competitiveness.
[0237] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A honeycomb catalyst for synergistic removal of VOCs and NOx at low temperature, characterized in that: The raw and auxiliary materials of the honeycomb catalyst include: an active component precursor, a carrier component and a strength auxiliary material; the mass ratio of the active component precursor, the carrier component and the strength auxiliary material is 8-20:55-75:15-30; The active component precursor is a co-precipitate of acid salts of copper, manganese and cerium; The strength auxiliary material is glass fiber treated with a coating liquid containing silicon and titanium elements.
2. The honeycomb catalyst according to claim 1, characterized in that: The carrier component is active titanium dioxide.
3. A method for preparing a honeycomb catalyst for synergistic removal of VOCs and NOx at low temperature, comprising the following steps: 1) Preparing an active component precursor: adding a coprecipitant to a mixed solution containing a copper salt, a manganese salt, and a cerium salt to obtain a coprecipitate of copper, manganese, and cerium salts, and filtering and removing the liquid to obtain an active component precursor; 2) Preparing strength auxiliary materials: soaking glass fiber in a coating liquid containing silicon and titanium elements, and taking it out to obtain strength auxiliary materials; 3) preparing a clay material: adding the active component precursor obtained in step 1), the strength auxiliary material obtained in step 2), and the molding auxiliary agent to the carrier component in order to obtain a clay material; 4) preparing a honeycomb catalyst blank: the clay obtained in step 3) is kneaded, moved into a mold and extruded to obtain a honeycomb catalyst blank; 5) Drying and calcining: The honeycomb catalyst blank obtained in step 4) is aged, dried, baked, and calcined to obtain a honeycomb catalyst.
4. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of the total amount of copper, manganese and cerium in the coprecipitant and the mixed solution is 1.05 to 1.2:1; The temperature of the coprecipitant is controlled at 38-80°C; the reaction temperature of the mixed solution is controlled at 45-80°C; the reaction time of the coprecipitant solution and the mixed solution is 0.2-1.5h; The mass fraction of the acid salt co-precipitate after pressure filtration and deliquoring is controlled to be 65% to 85%; Preferably, the concentration of the coprecipitant is 550-620 g / L; Preferably, the total mass fraction of copper salt, manganese salt and cerium salt in the mixed solution is 200-280 g / L; the molar ratio of copper salt, manganese salt and cerium salt is 1-3:1-3:4-8.
5. The preparation method according to claim 4, characterized in that: The coprecipitant is an oxalic acid aqueous solution or an ammonium carbonate solution; The mixed solution is obtained by dissolving acid salts of copper, manganese and cerium in a mixed solvent of water, ethanol and glycerol; Preferably, the acid salt of copper, manganese and cerium comprises acetate of copper, manganese and cerium and / or nitrate of copper, manganese and cerium; Preferably, the acetates of copper, manganese and cerium comprise: hydrated copper acetate, hydrated manganese triacetate and hydrated cerium acetate; Preferably, the nitrates of copper, manganese and cerium comprise: copper nitrate, manganese nitrate and cerium nitrate; Preferably, the mass ratio of water, ethanol and glycerol in the mixed solvent is 100:10-25:3-15.
6. The preparation method according to claim 1, characterized in that: In step 2), the glass fiber is immersed for 0.2 to 1 hour, and the weight gain of the glass fiber after coating is controlled to be 5% to 25%; The mass fraction of silicon in the coating liquid is 5% to 12%, and the mass fraction of titanium is 7% to 18%; Preferably, the coating liquid is composed of a titanium affinity agent, a wetting and dispersing agent and a first solvent, and the mass ratio thereof is 0.3-2:0.5-3:1; Preferably, the titanophilic agent comprises a titanate ester, which is a mixture of one or more of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropoxy titanium and isooctyl titanate; Preferably, the wetting and dispersing agent comprises alkoxysilane, which is a mixture of one or more of octadecyltrimethoxysilane, n-octyltriethoxysilane, n-hexyltriethoxysilane, tetraethoxysilane, tetrabutoxysilane and methylsilane; Preferably, the first solvent is glycerol or a non-aqueous solvent containing glycerol.
7. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of the active component precursor, the carrier component, the strength auxiliary material and the molding auxiliary agent is 8-20:55-75:15-30:4-10; Preferably, the molding aid comprises a pH adjuster, a lubricant, a pore former, and a second solvent; Preferably, the pH adjuster includes one of sodium hydroxide, ammonia water or liquid ammonia, and the pH value is between 8 and 12; Preferably, the lubricant is epoxy oleate or phthalate, and the amount of the lubricant added is 0.1% to 0.4% of the mass of the carrier component; Preferably, the pore-forming agent is biomass fiber powder, and the amount of the pore-forming agent added is 1% to 3% of the mass of the carrier component; Preferably, the second solvent is a liquid mixed with glycerol and water in a mass ratio of 0.5 to 3:
1.
8. The preparation method according to claim 1, characterized in that: In step 5), aging and drying: placing the honeycomb catalyst blank in an environment of 45 to 60° C. for 24 to 72 hours, and controlling the relative humidity at 85% to 95%; The drying temperature is 105-130°C and the drying time is 3-24 hours; The calcination temperature is 350-480°C, the calcination time is maintained at 1-6 hours, and the heating rate is 1-10°C / min.
Citation Information
Patent Citations
Honeycomb integral type low temperature denitrifying catalyst and preparation method thereof
CN105727985A
Monolithic low-temperature manganese / cerium honeycomb denitration catalyst
CN117019136A
